2012
DOI: 10.5194/hess-16-1481-2012
|View full text |Cite
|
Sign up to set email alerts
|

On the uncertainties associated with using gridded rainfall data as a proxy for observed

Abstract: Abstract. Gridded rainfall datasets are used in many hydrological and climatological studies, in Australia and elsewhere, including for hydroclimatic forecasting, climate attribution studies and climate model performance assessments. The attraction of the spatial coverage provided by gridded data is clear, particularly in Australia where the spatial and temporal resolution of the rainfall gauge network is sparse. However, the question that must be asked is whether it is suitable to use gridded data as a proxy … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(93 citation statements)
references
References 15 publications
4
88
0
1
Order By: Relevance
“…This spatially interpolated gridded data may introduce some artificiality and make it difficult to verify the "validity" of the gridded data values in regions or periods with none or sparse rain gauges [22,23]. However, the CGDPA data were used only as a benchmark for the spatial comparison of daily mean precipitation values with satellite products.…”
Section: Ground Reference Datamentioning
confidence: 99%
“…This spatially interpolated gridded data may introduce some artificiality and make it difficult to verify the "validity" of the gridded data values in regions or periods with none or sparse rain gauges [22,23]. However, the CGDPA data were used only as a benchmark for the spatial comparison of daily mean precipitation values with satellite products.…”
Section: Ground Reference Datamentioning
confidence: 99%
“…Therefore, in order to provide a spatial/geographical context to the recent dry conditions in SEA, and to ensure limitations of gridded rainfall data sets are not skewing our results (see Tozer et al, 2012), station-based rainfall data from regions south of 30 degrees (shown in Fig. 1a) from the following data sets was also used: 1994-2009 compared to 1948-1993), (b) precipitable water (1994-2009 compared to 1948-1993), (c) surface precipitation rate (1976-1993 compared to 1948-1975) and (d) precipitable water (1976-1993 compared to 1948-1975).…”
Section: Station-based Rainfall Datamentioning
confidence: 99%
“…The year 1976 was chosen as the start year of this analysis, as this corresponds to a statistically significant change in ocean/atmosphere processes and a reorganisation of the climate system (Mantua et al, 1997). Tozer et al (2012), and other references reviewed within, demonstrate that gridded rainfall data sets often do not capture extreme events particularly well (due to smoothing during the interpolation process, inadequate representation of topographical effects, uncertainties associated with remotely sensed data, density of available station data that varies in space and time, etc.). Further, as mentioned in Sect.…”
Section: Setting the Context Of Recent Dry Conditions In Sea In Termsmentioning
confidence: 99%
“…However, this paper focuses only on rainfall patterns and large-scale changes in ECL behaviour so care should be taken, for example, when using the insights here to develop inputs for hydrological modelling as the AWAP dataset has documented limitations and uncertainties, especially at higher elevations and/or in areas or time periods where gauged information is sparse (e.g. Jones et al 2009, Tozer et al 2012, King et al 2013). Figure 2 shows the frequency of occurrence for each of the five different ECL sub-types within the different months of the year.…”
Section: Relationship Between Ecls and Esa Rainfallmentioning
confidence: 99%
“…To allow easier visualisation of spatial patterns, gridded daily rainfall data from the Australian Water Availability Project (AWAP; Jones et al 2009), a joint initiative of the BOM and the Commonwealth Scientific and Industrial Research Organisation (CSIRO) was also used (refer to Tozer et al 2012 for discussion on why both observed rainfall data, i.e. obtained directly from rainfall stations, and gridded AWAP data should be used).…”
Section: Relationship Between Ecls and Esa Rainfallmentioning
confidence: 99%